The Influence of Audit Committee Characteristics on Firm Profitability in Ghana - Musah, Alhassan; Ayaiga, Charles; Blay, Marshall Wellington; Okyere, Daniel Odei (The Indonesian Journal of Accounting Research, 2025)
This study explored how audit committee characteristics—specifically independence, meeting frequency, size, and financial expertise—affect the profitability of companies listed on the Ghana Stock Exchange. Using secondary data from industrial firms spanning 2010 to 2020, the research focused on Return on Assets (ROA) as the key performance measure. The independent variables were AC size, financial expertise, meeting frequency, and independence. The findings revealed a statistically significant positive relationship between ROA, AC independence, and financial expertise. However, the results also indicated a significant negative correlation between audit committee size and firm performance (FP), suggesting that larger committees may hinder profitability. The study underscored the critical role of independent and financially knowledgeable audit committees in enhancing corporate governance and improving financial outcomes for publicly listed firms in Ghana. These findings emphasize the importance of robust audit committee features in promoting transparency, accountability, and better financial performance for industrial companies on the Ghana Stock Exchange.